Upregulation of cytochrome c oxidase subunit 6b1 (Cox6b1) and formation of mitochondrial supercomplexes: implication of Cox6b1 in the effect of calorie restriction - Kim, Sang-Eun (Age (Dordr), 2015)
Calorie restriction (CR), a non-genetic intervention that promotes longevity in animals, may exert anti-aging effects by modulating mitochondrial function. Based on our prior mitochondrial proteome analysis, we focused on the potential roles of cytochrome c oxidase (Cox or Complex IV) subunit 6b1 on formation of mitochondrial supercomplexes comprised of Complex I, III, and IV. Blue native polyacrylamide gel electrophoresis followed by immunoblotting showed that the amount of Cox6b1 and the proportion of high molecular weight supercomplexes (SCs) comprised of Complexes I, III, and IV were increased in the liver of mice subjected to 30 % CR, compared with the liver of mice fed ad libitum. In in vitro experiments, in Cox6b1-overexpressing NIH3T3 (Cox6b1-3T3) cells, Cox6b1 was increased in the SC, III(2)IV(1), and III(2)IV(2) complexes and Cox was concomitantly recruited abundantly into the SC, compared with control (Con)-3T3 cells. The proportions of III(2)IV(1), and III(2)IV(2), relative to IV monomer were also increased in Cox6b1-3T3 cells. Cox6b1-3T3 cells showed increased oxygen consumption rates, Cox activity, and intracellular ATP concentrations, indicating enhanced mitochondrial respiration, compared with Con-3T3 cells. Despite the increased basal level of mitochondrial reactive oxygen species (ROS), cell viability after inducing oxidative stress was greater in Cox6b1-3T3 cells than in Con-3T3 cells, probably because of prompt activation of protective mechanisms, such as nuclear translocation of nuclear factor E2-related factor-2. These in vivo and in vitro studies show that Cox6b1 is involved in regulation of mitochondrial function by promoting the formation of SC, suggesting that Cox6b1 contributes to the anti-aging effects of CR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11357-015-9787-8) contains supplementary material, which is available to authorized users.